PENERAPAN MEDIA POWERPOINT INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP INDIKATOR MENAFSIRKAN DAN MENGKLASIFIKASIKAN PADA MATERI ALAT OPTIK SISWA MAS PP DAARUN NAHDHAH TAWALIB BANGKINANG - Isni Syahadah; Z. Zulirfan Z. Zulirfan; Naila Fauza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The use of interactive powerpoint media in physics learning aims to improve students' conceptual understanding. Interpreting and classifying is an indicator of concept understanding that can help improve students' understanding of physics concepts, one of which is optical instrument material. The purpose of this study was to describe students' conceptual understanding of indicators of interpreting and classifying through the application of interactive powerpoint media to class XI optical instrument material at MAS PP Daarun Nahdhah Tawalib Bangkinang. There were 62 students who participated in this study in class XI MIPA in the even semester of the 2021/2022 academic year at MAS PP Daarun Nahdhah Tawalib Bangkinang, Kab. Kampar, Prov. Riau. The type of research used was quasi-experimental with a non-equivalent posttest only control group design that involved 2 classes, namely the experimental class and the control class. The experimental class was given treatment with the application of interactive powerpoint media while the control class used conventional learning. Based on the results of the students' conceptual understanding test on the indicators of interpreting and classifying, it was found that the average value of students' absorption in the experimental class was higher than the control class. The average value of the absorption power of the experimental class is 77,2 so that it is in the good category, while the average concept understanding test of the control class students on the indicators of interpreting and classifying is 63.3 and is in the good enough category. Therefore, it can be concluded that the application of interactive powerpoint media can improve students' conceptual understanding of the optical instrument material XI MAS PP Daarun Nahdhah Tawalib Bangkinang with good absorption category.Keywords: Interactive Powerpoint Media, Concept Understanding, Optical Instrument, Physics Learning